Management of the Robster farming industry in Nakhon Pathom Province - Mangwaen, Weerachet; Sonong, Sirion; Poojom, Nipawan; Sutthachaidee, Wannee; Poobt, Kulnipa (Journal of Industrial Business Administration, 2024)
This research is quantitative research that aims to study the objective is to study the supply chain, problems, obstacles or limitations of the lobster supply chain in the Nakhon Pathom province of Thailand. Study appropriate strategies and propose guidelines using random sampling and collect data by answering questionnaires.Total number: 400 sample ponds. then the analysis was done with descriptive statistics, finding frequencies, percentages, and inferential statistics, including analyzing assumptions and relationships among various factors that affect problems and obstacles in shrimp farming among a sample of farmers using the Chi-square test and determining appropriate strategies for the lobster industry in Anakhon Pathom Province. From the results it can be 1.) Lobsters still encounter problems in terms of hygiene and water quality in clay lobster ponds. Sanitation and disease prevention are the main ones. next is the problem of the spread of pathogens in shrimp farming. This causes the earthen ponds to raise giant freshwater prawns and shrimp farming. 2.) From the analysis of assumptions and relationships among various factors using the Chi-square test. It was found the number of people who can help with work and experience in raising lobster. temperature change in water there is no relationship with the problems and obstacles in raising lobster. Whilethe price factor Structure of the lobster farming industry while the price factor Structure of the lobster farming industry and demographics and clay ponds for raising lobsters are significantly related to problems and obstacles in shrimp farming. 3.) Developing commercial lobster production to meet standards and safety. Developing and processing products made from lobster to farmers and entrepreneurs. and promoting the lobster market in Nakhon Pathom Province will help add economic value to the province. It is a strategy suitable for the lobster industry in Nakhon Pathom Province.